Mesocolon Cyst, Case Report and Literature Review - Romero-Briones, Carlos Gabriel; Ponciano-Guerrero, Mateo; Ramírez-Vázquez, Jose Luis; Flores-García, Alba Elda; Montenegro-Jiménez, Carolina; Martínez-Romero, Jose Alfonso (British Journal of Healthcare and Medical Research, 2023)
Introduction: They commonly originate in the mesentery of the small intestine (70%), although a proportion has been found to originate in the mesocolon (24%) and the retroperitoneum (14.5%). Clinical case: 58-year-old female patient. The intervention was performed by performing exploratory laparotomy, dissecting by planes, cavity with no signs of tumor activity, exposure of the sigmoid colon, following its hilum, a tumor was found in the mesentery, the cyst measuring 150 x 130 mm. solid cystic appearance. Discussion: A definitive diagnosis is established through surgical excision and with a definitive study such as histopathological examination of the tumor. All of these considerations were taken into account in the management of our case. Conclusions: Regarding the sigmoid mesocolon cyst, it is a rare and mostly benign pathology, with an asymptomatic course and if symptoms are present, it is not very specific, and therefore there is a delay in the diagnosis.